The Relationship between Financial Constraints and the Value of Cash Holding: An Empirical Investigation of the North America - Wang, Jiayu (2018)
The main purpose of this dissertation is to explore the relationship between cash holding and financial constraints based on two type of companies, which are financial constrained companies and financial unconstrained companies. The sample is selected from all industries in the North America (exclude the financial industry and the utility industry). There are three proxies are chosen to classify the sorts of companies, and three regression model are conducted to examine the impacts of cash holdings on both types of enterprises. The empirical results demonstrate that for the reason of difficulties in entering external capital market, financial constrained firms tend to hold more cash from cash flow to satisfy their company’s growth and investment opportunities, compared to firms without financial friction.